Impact of Variations in Rabbit Urine Fertilizer Dosage on Corn Fodder (Zea mays) productivity - Ludfia Windyasmara; Ahimsa Kandi Sariri; Pradapa, Ringga Ardha Toni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Corn is a ruminant animal feed with high vegetable protein and carbohydrate values. Because corn growers need a large area of land, one alternative is corn fodder. The application of corn fodder is very simple, harvests quickly and saves land. To support the growth of corn fodder, adequate nutrition is needed. Rabbit urine organic fertilizer contains high levels of N, P and K nutrients to increase plant productivity. This study aims to determine the effect of different doses of rabbit urine on the productivity of corn fodder (Zea mays). The method in this research is the research method used in this research is the Completely Randomized Design Method (CRD) which consists of 4 treatments, namely the concentration of rabbit urine fertilizer. Rabbit urine fertilizer concentrations consisted of 7 ml, 14 ml and 21 ml. Harvested on day 14. The parameters observed were plant height, number of leaves, wet biomass and dry biomass. Based on the results of this research, it can be concluded that the use of rabbit urine fertilizer in corn fodder at the average plant height P0=10.32 P1=11.85 P2=11.44 P3=13.67. The mean number of leaves P0=1.64 P1=1.73 P2=1.69 P3=1.81. The mean for wet biomass P0=57.37 P1=71.14 P2=74.09 P3=86.65. The average dry biomass, namely P0=6 P1=11 P2=11.40 P3=17.40. The conclusion from this research is that corn fodder given rabbit urine fertilizer has a very significant effect (P<0,01) on plant height, number of leaves, wet biomass and dry biomass.